Financial Decisions: A Phenomenological Study on Small-Scale Buddhist Entrepreneurs - Mahadewi, Lufina; Surachman, Surachman; Hadiwidjojo, Djumilah; Indrawati, Nur Khusniyah (Sekolah Tinggi Manajemen IPMI, 2024)
ABSTRACT Religious values are contexts in social science used to explain the irrational behaviour of psychological factors in financial decision-making . The aim of the study is to explore how religious values drive financial decisions through an interpretive paradigm to capture the role of the cognitive dimension of religion and its values. The setting of this study was conducted in Bekasi, West Java. This study reveals that Buddhist entrepreneurs are individuals who intrinsically build a cultural system, one of which is religion and its values, which play a role in shaping entrepreneurial behaviour and entrepreneurial financial decisions. This study reveals that the entrepreneurial activities carried out by Buddhist entrepreneurs play a role in the dynamics of the structure of the social life of Buddhist entrepreneurs, which focuses on creating alignment of entrepreneurial goals with the fulfillment of socio-religious factors. Keywords: Financial Decision, Buddhist Values, Buddhist Entrepreneurship